Do nonreciprocal preference regimes increase exports? - Salvador Gil Pareja; José Antonio Martínez Serrano (European Regional Science Association (ERSA), 2011)
This paper investigates whether and to what extent nonreciprocal preference regimes have increased developing countries' exports to richer countries. Moreover, it analyzes how they have affected donors' exports to beneficiary countries. Using recent developments in the econometric analysis of the gravity equation over the period 1990-2008, we find robust evidence that, on the whole, nonreciprocal preference regimes and GSP schemes have had an economically significant effect on exports from developing countries. However, the estimation of catch-all dummies masks heterogeneous results for the individual schemes. Finally, we find that nonreciprocal regimes have also increased exports from donors to beneficiary countries.
Keywords: 330